2004
DOI: 10.1002/job.258
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling task and relationship conflict: the role of intragroup emotional processing

Abstract: SummaryThe present paper focuses on the role of emotion in intragroup conflict processes. We propose that how group members handle emotion affects intragroup interactions and has implications for task and relationship conflict. Three types of variables-collective emotional intelligence, intragroup relational ties, and conflict-relevant interactional norms-constrain negative emotionality and may determine whether task conflict results in damaging relationship conflict. The moderating influence of these variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
266
0
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(293 citation statements)
references
References 64 publications
8
266
0
11
Order By: Relevance
“…It is commonly believed that an individual's characteristics during task performance is influenced by factors such as team conflict norms, individual characteristics, work structure, team characteristics, task characteristics and the interaction among these input characteristics. The conceptual framework of these parameters will greatly influence each other, as previously reported by Yang and Mossholder (2004), Ashkanasy and Daus (2002), Bodtker and Jameson (2001), which suggest the connection between work place conflict and emotions.…”
Section: Task Conflict In Teamsmentioning
confidence: 60%
“…It is commonly believed that an individual's characteristics during task performance is influenced by factors such as team conflict norms, individual characteristics, work structure, team characteristics, task characteristics and the interaction among these input characteristics. The conceptual framework of these parameters will greatly influence each other, as previously reported by Yang and Mossholder (2004), Ashkanasy and Daus (2002), Bodtker and Jameson (2001), which suggest the connection between work place conflict and emotions.…”
Section: Task Conflict In Teamsmentioning
confidence: 60%
“…conflict escalation, see Glasl, 1982;Pruitt, 2008). In a similar vein, research has shown that effective conflict management also involves managing potentially negative emotions arising from workplace conflict, thereby minimising the potential for escalation (Ayoko, Callan, & Hartel, 2008;Curseu, Boros, & Oerlemans, 2012;Yang & Mossholder, 2004).…”
Section: The Dual-concern Model Of Conflict Resolutionmentioning
confidence: 99%
“…Conflicts can escalate to more destructive levels when workers are not capable of reducing the emotional intensity inherent in all conflicts (Ayoko et al, 2008;Curseu et al, 2012;Yang & Mossholder, 2004). In such situations, the parties affected usually turn to external agents for resolution (i.e.…”
Section: The Dual-concern Model Of Conflict Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that supports the traditional view that conflict is dysfunctional, especially those that arise from relationships. This is because relationship conflicts are often negative as they tend to hinder cooperation and reduce mutual understanding and trust (Yang & Mossholder, 2004). Studies, as shown in the IPMA-HR 2006 survey (as cited in Robbins & Judge, 2009) reveal that approximately 20 percent of organizational resources are often used up in resolving conflicts arising from interpersonal relationship issues.…”
Section: Theoretical Backgroundmentioning
confidence: 99%